Metal–Organic Frameworks for Electrocatalysis: Beyond Their Derivatives. Issue 12 (15th December 2021) - Yang, Yongchao; Yang, Yuwei; Liu, Yangyang; Zhao, Shenlong; Tang, Zhiyong
Abstract : Metal–Organic Frameworks for Electrocatalysis Metal–organic frameworks (MOFs) are an emerging family of catalytic materials used in many energyconversion processes. In article number 2100015, Yongchao Yang, Shenlong Zhao, Zhiyong Tang, and co‐workers comprehensively summarize the unique physicochemical superiorities and latest development of pristine MOF‐based electrocatalysts. A systematic outline of their recent advances in electrocatalysis is presented, and the main challenges and prospects for the future are highlighted.